1994
DOI: 10.1093/oxfordjournals.jbchem.a124298
|View full text |Cite
|
Sign up to set email alerts
|

Histidinol Dehydrogenase Loses Its Catalytic Function through the Mutation of His261→Asn Due to Its Inability to Ligate the Essential Zn

Abstract: Histidinol dehydrogenase (HDH), a Zn-metalloenzyme, produces His from histidinol through two successive oxidation reactions with NAD+ as a coenzyme. A mutation, His261-->Asn, caused the complete loss of the Zn, thereby inactivating the enzyme, without significant structural perturbation. The ability to oxidize an intermediate, histidinaldehyde, was restored to about 4% of that of the wild-type enzyme by adding 0.5 mM MnCl2, whereas the histidinol oxidation activity could not be recovered with the mental additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…The Zn 2ϩ ligand atom distances are within the expected limits (41). The presence of His-262 and His-419 in the Zn 2ϩ coordination environment is consistent with previous mutagenesis experiments (15). NMR experiments (16) suggested that the amino group of the ligand (including L-histidinol, histamine, and L-histidine) is not involved in Zn .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The Zn 2ϩ ligand atom distances are within the expected limits (41). The presence of His-262 and His-419 in the Zn 2ϩ coordination environment is consistent with previous mutagenesis experiments (15). NMR experiments (16) suggested that the amino group of the ligand (including L-histidinol, histamine, and L-histidine) is not involved in Zn .…”
Section: Resultssupporting
confidence: 86%
“…The Zn 2ϩ ion is essential for enzymatic activity, although other metals such as Mn in forming an active enzyme (13). Biochemical and mutagenesis studies on HisD from S. typhimurium (12,14) and Brassica oleracea (15) have identified two histidine residues, corresponding to His-262 and His-419 from E. coli, as part of the active site, although the precise role of His-262 has not been established (14)(15)(16). NMR measurements indicated that the substrate participates in Zn 2ϩ coordination through its imidazole ND1 and alcohol oxygen atoms (16), and Zn 2ϩ has been proposed to participate directly in catalysis (14,16).…”
mentioning
confidence: 99%
“…The oxidation of histidinol to histidinal is reversible, while that of histidinal to His is not, and a low dissociation constant for the histidinal-HDH complex explains the failure to detect free histidinal (Kheirolomoom et al, 1994). Site directed mutagenesis studies have established that Cys residues conserved between the cabbage and S. typhimurium HDH enzymes are not required for catalytic activity, while His261 is absolutely required as a Zn 2+ binding ligand (Nagai et al, 1993;Nagai and Ohta, 1994). Subsequent NMR studies revealed that Zn 2+ is present in the active site of the HDH enzyme and is required for substrate binding (Kanaori et al, 1996).…”
Section: The Histidine Biosynthetic Pathwaymentioning
confidence: 99%
“…In histidinol dehydrogenase, replacing the zinc ligand His 261 with asparagine results in the loss of both its zinc-binding capability and its enzymatic activity (Nagai & Ohta, 1994). In Bacillus stearothermophilus ADH, replacing Cys 38 with serine at the catalytic-zinc site abolishes all enzymatic activity, although the mutant is over-expressed as a folded protein (Sakoda & Imanaka.…”
mentioning
confidence: 99%